Comparison of Pyloric Intervention Strategies at the Time of Esophagectomy: Is More Better? - Antonoff, Mara B. (2014)
BACKGROUND: Controversy remains regarding the role of pyloric drainage procedures following esophagectomy with gastric conduit reconstruction. We aimed to compare the effect of pyloric drainage strategies upon subsequent risk of complications suggestive of conduit distention, including aspiration and anastomotic leak. METHODS: A retrospective study was conducted reviewing patients undergoing esophagectomy between 1/2007 – 4/2012. Prospectively collected data included baseline comorbidities, operative details, hospital course, and complications. Statistical comparisons were performed using ANOVA for continuous variables and X(2) testing for categorical variables. RESULTS: There were 361 esophagectomies performed during the study period, 68 were excluded from analysis (for prior esophagogastric surgery and/or benign disease). Among 293 esophagectomies included, emptying procedures were performed as follows: 44 (15%) no drainage procedure, 197 (67%) pyloromyotomy/pyloroplasty, 8 (3%) dilation alone, 44 (15%) dilation + onabotulinumtoxinA. Aspiration occurred more frequently when no pyloric intervention was performed (5/44 [11.4%] versus 6/249 [2.4%], P = 0.030). The incidence of anastomotic leak (18 [6.1%]) and gastric outlet obstruction (5 [1.7%]) were statistically similar among groups. Subgroup analysis demonstrated persistence of these findings when limiting the comparison to transthoracic esophagectomies. Major complications directly related to pyloroplasty/pyloromyotomy occurred in 2 (0.6%) patients, including 1 (0.3%) mortality. CONCLUSIONS: These data suggest that omission of pyloric intervention at the index operation results in more frequent aspiration events. The combination of dilation plus onabotulinumtoxinA provided for a similar complication profile compared to surgical drainage. Future prospective comparisons are needed to evaluate these short-term effects of pyloric intervention as well as long-term sequelae such as dumping syndrome and bile reflux.